IMPROVED Candida methylica FORMATE DEHYDROGENASE FERMENTATION THROUGH STATISTICAL OPTIMIZATION OF LOW-COST CULTURE MEDIA - Kahraman, Mustafa; Ordu, Emel Bicakci; Yesiladali, Koray; Karaguler, Nevin Gul; Tamerler, Candan (TAYLOR & FRANCIS INC, 2012)
NAD(+)-dependent formate dehydrogenase (FDH, EC 1.2.1.2) is of use in the regeneration of NAD(P)H coenzymes, and therefore has strong potential for practical application in chemical and medical industries. A low-cost production of recombinant Escherichia coli (E. coli) containing FDH from Candida methylica (cmFDH) was optimized in molasses-based medium by using response surface methodology (RSM) based on central composite design (CCD). The beet molasses as a sole carbon source, (NH4)(2)HPO4 as a nitrogen and phosphorus source, KH2PO4 as a buffer agent, and Mg2SO4 center dot 7H(2)O as a magnesium and sulfur source were used as variables in the medium. The optimum medium composition was found to be 34.694 g L-1 of reducing sugar (equivalent to molasses solution), 8.536 g L-1 of (NH4)(2)HPO4, 3.073 g L-1 of KH2PO4, and 1.707 g L-1 of Mg2SO4 center dot 7H(2)O. Molasses-based culture medium increased the yield of cmFDH about three times compared to LB medium. The currently developed media has the potential to be used in industrial bioprocesses with low-cost production.
Keywords: biocatalyst preparation; Candida methylica; culture media; formate dehydrogenase; statistical optimization; ACID PRODUCTION; MOLASSES; SUGAR; TAG; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology